Women in the light of the archives of Shubat-Enlil "Tell Lilan" from the 18th century BC. - mohammad, jihan (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The city of Shubat-Enlil, which was discovered decades ago at the site of Tell Leilan in the Syrian Jazira, southeast of the city of Qamishli, is one of the most prominent ancient cities in northern Mesopotamia, It was the center of a kingdom called Apum, and it extended widely, including the eastern part of the upper island known in ancient historical studies as the Khabur triangle, and it controlled the traveling trade caravan routes between the Assyrian capital, Ashur, in the east, and the commercial settlement of Kanish, in central Anatolia. Several thousand documents written in cuneiform and the Akkadian language, dating back to the eighteenth century BC, were discovered at the site. It includes abundant information about the economic and social life within the Kingdom and its external relations with neighboring regions. Therefore, we believe that it can be a model that shows us the situation of women in that region at that time.